Ecological aspects of the arid and semi-arid truffle in Turkey: evaluation of soil characteristics, morphology, distribution, and mycorrhizal relationships - Akyuz, Mehmet; Kirbag, Sevda; Kursat, Murat (Tubitak Scientific & Technological Research Council Turkey, 2012)
We undertook an evaluation of the physical and chemical quality of soil characteristics, micro- and macroscopic features of morphology, distribution, and mycorrhizal relationships of Terfezia boudieri Chatin. The topsoil was found to be 54.73% sand, 21.97% clay, 23.30% dust, 45.27% dust-clay, 0.126% nitrogen, 1.848% organic matter, and 3.78% total lime. Investigations revealed that the soil contained 40.92 ppm P2O5, 613.0 ppm K2O, 28.82 ppm Na, and 0.164 mmhos/cm salt. It had a pH of 7.12 and the soil type was determined to be sand-clay-slimy. Various characteristics were recorded including ascocarp features (hypogeous, like tubers) and colour (peridium, glebe red tones), occurrence frequency (infrequent), time of appearance (March to May), host (Helianthemum salicifolium (L.) Miller), traditional uses (food, aphrodisiac), eating quality (excellent), habitat (basic soil, sand-clay-slimy, and semi-arid zone), fresh weight (20-150 g) and ascospore morphology (reticulate and warty spherica, 15-18 mu m, medium size). In conclusion, the habitats of T boudieri and H. salicifolium should be protected by turning those fields into natural protected areas.
Türkiye'de kurak ve yarı kurak alanlardaki yer mantarına ekolojik bakış: Toprak karakteristikleri, morfoloji, da?ılımları ve mikorizal ilişkilerinin de?erlendirilmesi
Keywords: Biodiversity; Helianthemum; truffle; mushroom; mycorrhiza; Terfezia